The Opportunity to Access Better Information Technology - Eri Mardison (Jurnal Teknologi Informasi dan Pendidikan, 2021)
Children are born without being able to choose a number of factors that are attached to them. This is in fact unfair to him in supporting his future. HOI exists to calculate a number of factors that cause imbalance and how much inequality should be reallocated. The usage of cellphone has covered 63.86 percent. The inequality that must be reallocated is 8.76 percent. Per capita income and residence are the dominant influencing factors. In the case of cellphone ownership, the coverage was still 33.12 percent, with an inequality reallocation of 17.05 percent. Per capita income and residence are the dominant factors. Access coverage on new computers reached 17.35 percent with reallocation of inequalities reaching 28.87 percent. Per capita income, residence and certificate of household head are the dominant factors. Meanwhile internet access has covered 35.02 percent with inequality reallocation reaching 17.85 percent. Per capita income, residence and certificate of household head are the most dominant things. An understanding of reality is very important in taking online policies against children that happen to be implemented during the Covid-19 period and possibly afterward.